Coated particles and conductive materials containing same

By fixing a compound with an electric functional group on uneven silica particles, the adhesion between insulating and conductive particles is enhanced, addressing the challenges of conductivity reliability and insulation properties in coated particles.

JP7655745B2Active Publication Date: 2025-04-02NIPPON CHEMICAL IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021036851
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-04-02
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

There is a challenge in improving the adhesion between insulating particles and conductive particles in coated particles, which affects the reliability of conductivity and insulation properties.

Method used

The use of silica particles with uneven surfaces, where a compound containing an electric functional group or its condensate is fixed, enhances the adhesion between insulating and conductive particles, improving conductivity reliability.

Benefits of technology

This approach results in coated particles with excellent adhesion and conductivity reliability, effectively addressing the challenges of short circuits and insulation issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655745000010
    Figure 0007655745000010
  • Figure 0007655745000001
    Figure 0007655745000001
  • Figure 0007655745000002
    Figure 0007655745000002
Patent Text Reader

Abstract

To provide coated particles having excellent adhesiveness and conduction reliability between insulating particles and conductive particles, and a conductive material containing the coated particle.SOLUTION: Provided is a coated particle obtained by coating a surface of a conductive particle having a metal film formed on a surface of a core particle with an insulating particle, in which, in the insulating particle, a compound or a condensate thereof containing a functional group having an electric charge is fixed on a surface of silica particles having irregularity on a surface. The core particles are preferably a resin or a composite material of an organic substance and an inorganic substance.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to coated particles in which conductive particles are coated with an insulating layer, and to a conductive material containing the same. [Background technology]

[0002] 2. Description of the Related Art Conductive particles, which are resin particles having metals such as nickel and gold formed on the surfaces thereof, are used as conductive materials such as conductive adhesives, anisotropic conductive films, and anisotropic conductive adhesives. In recent years, with the further miniaturization of electronic devices, the circuit width and pitch of electronic circuits are becoming smaller and smaller. Accordingly, conductive particles with small particle diameters are required for use in the above-mentioned conductive adhesives, anisotropic conductive films, anisotropic conductive adhesives, etc. When such small particle diameter conductive particles are used, the amount of conductive particles must be increased to improve the connectivity. However, when the amount of conductive particles is increased, a short circuit occurs due to conduction in an unintended direction, i.e., conduction in a direction different from that between the opposing electrodes, and it is difficult to obtain insulation in that direction. In order to solve this problem, insulating coated conductive particles are used in which the surfaces of the conductive particles are coated with an insulating material to prevent contact between the metal layers of the conductive particles.

[0003] For example, Patent Document 1 describes coated particles in which a particle having a surface made of a conductive metal is used as a core, and the surface of the particle is partially modified with organic particles made of an organic compound containing a functional group that has a binding ability to the metal, and it is described that the organic compound has a positive or negative charge.

[0004] Patent Document 2 describes coated particles similar to those described in Patent Document 1. The document describes that the coated particles form a single-layer coating layer by chemically bonding insulating fine particles to particles having a surface made of a conductive metal via functional groups that have binding properties to metals. The document describes that coated particles having such a configuration can be thermocompressed between electrodes to melt, deform, or peel off the insulating fine particles, thereby exposing the metal surface of the metal-coated particles, thereby enabling conduction between the electrodes and obtaining connectivity. Patent Documents 1 and 2 exemplify ammonium groups and sulfonium groups as the functional groups.

[0005] Patent Document 3 also describes that by applying insulating resin microparticles, which have on their surface a hetero element or functional group that has a bonding strength with a metal, to the surface of a metal-coated particle and then heating the applied particles, anisotropic insulating conductive particles having an insulating layer that does not have a particle shape on the surface of the metal-coated particle can be obtained. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2002 / 035555 Brochure [Patent Document 2] International Publication No. 2003 / 025955 Brochure [Patent Document 3] International Publication No. 2005 / 109448 Brochure Summary of the Invention [Problem to be solved by the invention]

[0007] In the case of conductive particles coated with insulating particles, the improvement of the adhesion between the insulating particles and the conductive particles has been an issue. The adhesion between the insulating particles and the conductive particles is important for achieving electrical conduction between the opposing electrodes while obtaining insulation in a direction different from that of the opposing electrodes (hereinafter, also referred to simply as connection reliability), so there is a demand for the development of coated particles with even better adhesion between the insulating particles and the conductive particles. In addition, since the conductive particles are displaced from the electrodes due to the mechanical force during thermocompression bonding, there is also a demand for improving the electrical conduction reliability.

[0008] Therefore, an object of the present invention is to provide coated particles which have excellent adhesion and conduction reliability between insulating particles and conductive particles, and a conductive material containing the same. [Means for solving the problem]

[0009] In view of the above-mentioned circumstances, the inventors have conducted extensive research and have discovered that in coated particles in which the surface of conductive particles having a metal film formed on the surface of a core material is coated with insulating particles, when the insulating particles are silica particles having an uneven surface to which a compound containing a charged functional group or a condensation product thereof is fixed, the coated particles have excellent adhesion between the insulating particles and the conductive particles and also have excellent conductivity reliability, thereby completing the present invention.

[0010] That is, the first invention that the present invention provides is a coated particle in which the surface of a conductive particle having a metal coating formed on the surface of a core particle is coated with an insulating particle, and the insulating particle is characterized in that a compound containing a functional group having an electric charge or a condensate thereof is fixed to the surface of a silica particle having an uneven surface.

[0011] A second aspect of the present invention is a conductive material comprising the coated particles of the first aspect of the invention and an insulating resin. Effect of the Invention

[0012] According to the present invention, it is possible to provide coated particles which have excellent adhesion between insulating particles and conductive particles and also have excellent electrical conductivity reliability. [Brief description of the drawings]

[0013] [Figure 1] TEM photograph (50,000x magnification) of the uneven silica particles used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described based on preferred embodiments. The coated particles of this embodiment are conductive particles having a metal coating formed on the surface of a core particle, the surface of which is coated with insulating particles, and the insulating particles are characterized in that a compound containing a functional group having an electric charge or a condensation product thereof is fixed to the surface of a silica particle having an uneven surface.

[0015] (Conductive particles) As the conductive particles, known particles that have been conventionally used in conductive adhesives, anisotropic conductive films, and anisotropic conductive adhesives can be used.

[0016] The core particles in the conductive particles may be inorganic or organic, without any particular limitations. Examples of inorganic core particles include metal particles such as gold, silver, copper, nickel, palladium, and solder, alloys, glass, ceramics, silica, metal or nonmetal oxides (including hydrates), metal silicates including aluminosilicates, metal carbides, metal nitrides, metal carbonates, metal sulfates, metal phosphates, metal sulfides, metal acid salts, metal halides, and carbon. On the other hand, examples of organic core particles include thermoplastic resins such as natural fibers, natural resins, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polybutene, polyamide, polyacrylic esters, polyacrylonitrile, polyacetal, ionomers, and polyesters, alkyd resins, phenolic resins, urea resins, benzoguanamine resins, melamine resins, xylene resins, silicone resins, epoxy resins, and diallyl phthalate resins. These may be used alone or in combination of two or more. A composite material of an organic substance and an inorganic substance may also be used. Examples include styrene-silica composite resin, acrylic-silica composite resin, crosslinked alkoxysilyl polymer-acrylic resin, polyorganosiloxane-silica, styrene-acrylate-silica composite resin, etc. Among these, core particles made of resin or a composite material of organic and inorganic substances are preferred because they have a smaller specific gravity than core particles made of metal, are less likely to settle, have excellent dispersion stability, and are easy to maintain electrical connection due to the elasticity of the resin. The composite material of organic and inorganic substances may have a core-shell structure.

[0017] When an organic substance is used as the core particle, it is preferable that the core particle does not have a glass transition temperature or that the glass transition temperature is greater than 100° C., since the shape of the core particle is easily maintained in the anisotropic conductive connection step and in the step of forming a metal film. When the core particle has a glass transition temperature, the glass transition temperature is preferably 200° C. or less, since the conductive particles are easily softened in the anisotropic conductive connection and the contact area is increased, making it easier to obtain electrical continuity. From this viewpoint, when the core particle has a glass transition temperature, the glass transition temperature is more preferably greater than 100° C. and less than 180° C., and particularly preferably greater than 100° C. and less than 160° C.

[0018] When an organic material is used as the core particle, if the organic material is a highly crosslinked resin, the glass transition temperature is hardly observed even when the measurement is attempted up to 200°C by the method described in the following examples. In this specification, such particles are also referred to as particles having no glass transition point, and such core particles may be used in the present invention. Specific examples of the core particle material having no glass transition temperature can be obtained by copolymerizing the monomer constituting the organic material exemplified above with a crosslinkable monomer. Examples of crosslinkable monomers include tetramethylene di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethylene oxide di(meth)acrylate, tetraethylene oxide (meth)acrylate, 1,6-hexane di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, tetramethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, Examples of such hard organic materials include polyfunctional (meth)acrylates such as glycerol di(meth)acrylate, glycerol tridi(meth)acrylate, etc., polyfunctional vinyl monomers such as divinylbenzene, divinyltoluene, etc., silane-containing monomers such as vinyltrimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, etc., and monomers such as triallyl isocyanurate, diallyl phthalate, diallyl acrylamide, diallyl ether, etc. In particular, in the field of COG (Chip on Glass), core particles made of such hard organic materials are often used.

[0019] There is no particular limitation on the shape of the core particles. In general, the core particles are spherical. However, the core particles may be in a shape other than spherical, such as fibrous, hollow, plate-like or needle-like, and may have a large number of protrusions on the surface or may be amorphous. In the present invention, spherical core particles are preferred because they have excellent filling properties and are easy to coat with metal.

[0020] The particle size distribution of the powder consisting of core particles measured by the above-mentioned method has a certain range. In general, the range of the particle size distribution of a powder is represented by the coefficient of variation shown in the following formula (1). Coefficient of variation (%) = (standard deviation / average particle size) × 100 (1) A large coefficient of variation indicates a wide distribution, while a small coefficient of variation indicates a sharp particle size distribution. In the present invention, it is preferable to use core particles having a coefficient of variation of 30% or less, particularly 20% or less, and especially 10% or less. The reason for this is that when the conductive particles of the present invention are used as conductive particles in an anisotropic conductive film, there is an advantage that the contribution ratio effective for connection is high.

[0021] In addition, there are no particular limitations on other physical properties of the core particles. However, when the core particles are resin particles, the value of K defined by the following formula (2) is 100 N / mm 2 ~100000N / mm 2and the recovery rate after 10% compressive deformation is preferably in the range of 1% to 100% at 20° C. By satisfying these physical property values, sufficient contact with the electrodes can be achieved without damaging the electrodes when they are pressure-bonded together. K value (N / mm 2 )=(3 / √2)×F×S -3 / 2 ×R -1 / 2 (2) (Here, F and S shown in formula (2) are the load value (N) and compression displacement (mm) at 10% compression deformation of the microsphere when measured using a microcompression tester MCTM-500 (manufactured by Shimadzu Corporation), and R is the radius of the microsphere (mm).)

[0022] The shape of the conductive particles is not particularly limited, although it depends on the shape of the core particles. For example, the conductive particles may be fibrous, hollow, plate-like, or needle-like, but spherical particles are preferred in terms of excellent packing properties and connectivity.

[0023] The conductive particles may have a smooth surface. Alternatively, the conductive particles may have a plurality of protrusions protruding from the surface. If the protrusions are a continuum made of the same material as the metal coating, the conductivity is further improved, which is preferable. More specifically, the metal coating has a flat portion and a plurality of protrusions protruding from the flat portion and forming a continuum from the flat portion, and the flat portion and the protrusions are preferably made of the same material. The term "continuum" means that the protrusions and flat portion of the metal coating are formed by a single process, and there is no part between the flat portion and the protrusions of the metal coating that impairs the sense of unity, such as a seam. However, with regard to the protrusions, the protrusions are made of a particle linkage formed by connecting a plurality of particles made of the material that constitutes the metal coating in a row, and it is acceptable for grain boundaries to be observed between the particles. Therefore, for example, when a core particle for forming a protrusion, such as a metal, a metal oxide, a non-metallic inorganic material such as graphite, or a conductive polymer is attached to the surface of a core particle, and the protrusion is formed from the core particle as a growth starting point, the flat portion and the protrusion are not formed in a single process, and therefore are not included in the continuum referred to in the present invention. However, it should be noted that a conductive particle having protrusions formed from such a core particle attached to a core particle and the core particle as a growth starting point is also within the scope of the present invention.

[0024] When the conductive particles have protrusions of the above-described configuration, the protrusions can break through the oxide film formed on the electrode surface when the electrodes are to be electrically connected, thereby reducing the connection resistance.

[0025] The height H of the protrusions is preferably 20 nm or more, particularly 50 nm or more, on average. The number of protrusions varies depending on the particle size of the conductive particles, but it is preferable that the number of protrusions is 1 to 20,000, particularly 5 to 5,000 per particle, from the viewpoint of further improving the conductivity of the conductive particles. The aspect ratio of the protrusions is preferably 0.5 or more, more preferably 1 or more. A large aspect ratio of the protrusions is advantageous because they can easily break through the oxide film described above. In addition, when an anisotropic conductive film is formed using conductive particles, it is believed that a large aspect ratio of the protrusions increases the resin rejection ability, resulting in high conductivity. The aspect ratio is the ratio of the height H of the protrusion to the length D of the base of the protrusion, i.e., the value defined as H / D.

[0026] The aspect ratio of the protrusions is as described above, and the length D of the base of the protrusions of the conductive particles is preferably 5 to 500 nm, particularly 10 to 400 nm, and the height H of the protrusions is preferably 5 to 500 nm, particularly 10 to 400 nm.

[0027] The metal coating in the conductive particles has electrical conductivity, and examples of the constituent metals include metals such as gold, platinum, silver, copper, iron, zinc, nickel, tin, lead, antimony, bismuth, cobalt, indium, titanium, antimony, bismuth, germanium, aluminum, chromium, palladium, tungsten, and molybdenum, as well as alloys thereof, and metal compounds such as ITO and solder. Among these, gold, silver, copper, nickel, palladium, and solder are preferred because of their low resistance, and nickel, palladium, gold, nickel alloys, palladium alloys, and gold alloys are particularly preferred because of their high binding with insulating particles. The metals in the conductive particles can be used alone or in combination of two or more. The nickel alloy also includes nickel-phosphorus, nickel-boron, and nickel-boron-phosphorus, and the palladium alloy also includes palladium-phosphorus and palladium-boron.

[0028] The metal coating may be a single layer structure or a laminated structure consisting of multiple layers. In the case of a laminated structure consisting of multiple layers, it is preferable from the viewpoint of reducing the connection resistance that the underlayer is made of nickel or a nickel alloy and the outermost layer is made of nickel, palladium, gold, a nickel alloy, a palladium alloy or a gold alloy, particularly when the metal coating is formed by electroless plating.

[0029] The thickness of the metal coating on the surface of the core particle is preferably 0.001 μm to 2 μm, and more preferably 0.005 to 1 μm.

[0030] Methods for forming a metal coating on the surface of core particles include dry methods using vapor deposition, sputtering, mechanochemical methods, hybridization methods, etc., and wet methods using electrolytic plating, electroless plating, etc. In addition, a metal coating may be formed on the surface of core particles by combining these methods, but conductive particles in which a metal coating is formed on the surface of core particles by electroless plating are preferred in that the particle surface can be uniformly and densely coated.

[0031] The average particle diameter of the conductive particles is preferably 0.1 μm or more and 50 μm or less, more preferably 1 μm or more and 30 μm or less. When the average particle diameter of the conductive particles is within the above range, the obtained coated particles do not cause a short circuit in a direction different from that between the opposing electrodes, and it is easy to ensure conduction between the opposing electrodes. In the present invention, the average particle diameter of the conductive particles is the average particle diameter measured using a scanning electron microscope (SEM). In addition, when the conductive particles are spherical in the scanning electron microscope image, the particle diameter measured using SEM is the diameter of a circular conductive particle image. When the insulating particles are not spherical, the particle diameter measured using SEM refers to the longest length (maximum length) of the line segments that cross the image of the conductive particles.

[0032] Specifically, the average particle size of the conductive particles is measured by the method described in the Examples.

[0033] Moreover, from the viewpoint of suppressing corrosion of electrodes and the like, it is preferable that the conductive particles contain few eluted impurity ions such as alkali metal ions, halogen ions, and organic acid ions.

[0034] The insulating particles used in the present invention are silica particles having an uneven surface, and a compound containing a charged functional group or a condensate thereof fixed to the surface of the silica particles.

[0035] The silica particles used in the present invention are silica particles having an uneven surface. The silica particles having an uneven surface are obtained by bonding small silica particles to the surface of large silica particles, and the large silica particles having uneven surfaces caused by the small silica particles are preferably used.

[0036] The particle size of the large silica particles is 50 to 500 nm, preferably 60 to 250 nm, as determined by TEM observation. When the average particle size of the large silica particles is within the above range, the insulating particles are easily adsorbed to the conductive particles in a uniformly dispersed state on their surfaces.

[0037] In addition, the particle diameter of the small silica particles is 3 to 30 nm, preferably 3 to 10 nm, in terms of average particle diameter determined by TEM observation, from the viewpoints of providing excellent adhesion between the insulating particles and the conductive particles, suppressing displacement of the conductive particles from the electrodes due to mechanical forces during thermocompression bonding of the electrodes, and providing excellent conduction reliability.

[0038] The ratio of the large silica particles to the small silica particles is preferably 10 to 80 parts by weight, and more preferably 20 to 80 parts by weight, of the small silica particles per 100 parts by mass of the large silica particles, from the viewpoint of obtaining insulating particles with a higher coverage rate than silica particles with a smooth surface.

[0039] The silica particles having an uneven surface can be produced by a known method (for example, see JP 2013-227168 A). For example, a particle binder is added to colloidal silica consisting of the large silica particles and the small silica particles to bond the small particles to the surfaces of the large particles, and active silicic acid is further added under heating to integrate the particles.

[0040] The binder may be an aluminum compound such as sodium aluminate or an aluminum halide compound. The amount of aluminum compound added is calculated based on the specific surface area of ​​the large silica particles. For example, colloidal silica containing 100 g of 50 nm silica particles as SiO2 has a specific surface area of ​​54.4 m 2 / g, so the total specific surface area is 5440 m 2 , i.e. 5.44 × 10 21 nm 2 , silanol group density is 8 / nm 2 So, the total number of silanol groups is 4.35 × 10 22 10% of the total silanol groups are aluminate ions Al(OH) 4- is bonded, the amount of aluminate ions is 4.35 x 1021, which converts to 0.0073 mol in molar terms, and the amount of sodium aluminate used is 0.74 g as Al2O3.

[0041] Next, active silicic acid is added to integrate the particles, and the amount of active silicic acid added can be calculated based on the particle size of the large silica particles. The amount of active silicic acid added must contain silica equivalent to increasing the particle size of the large silica particles by 3 to 7 nm. If the amount of active silicic acid added is less than 3 nm, the bonds are easily broken. If it is more than 7 nm, the degree of unevenness is small and the difference in performance with silica particles with a smooth surface becomes unclear. It is more preferably 4 to 6 nm.

[0042] The activated silicic acid is added under heating. This is the same as the build-up process for colloidal silica, where a mixture of two types of silica particles (large and small) and a binder is heated to 60-100°C, and while maintaining that temperature, it is added at a rate that allows the silica component of the activated silicic acid to cover the bonds between the large and small particles. While adding the activated silicic acid, an alkaline agent is added at the same time to keep the pH of the solution at 9-11. Examples of alkaline agents that can be used include caustic soda, caustic potash, and tetramethylammonium hydroxide. By doing so, it is possible to obtain silica particles having an uneven surface.

[0043] In the compound containing a charged functional group to be fixed to the surface of the silica particle having an uneven surface, the charged functional group may be one having a positive charge or one having a negative charge. Examples of the positively charged functional group include a phosphonium group, an ammonium group, a sulfonium group, and an amino group. Examples of the negatively charged functional group include a carboxyl group, a hydroxyl group, a thiol group, a sulfonic acid group, and a phosphate group.

[0044] In the present invention, the charged functional group is preferably a group selected from a phosphonium group, an ammonium group, a thiol group, and a sulfonic acid group, from the viewpoint of achieving closer adhesion of the insulating particles to the conductive particles.

[0045] As the compound having a phosphonium group or an ammonium group, a compound represented by the following general formula (1) is preferable. [ka] (In the formula, Q represents a P atom or a N atom, and X represents a monovalent anion.) In the formula (1), R 1 , R 2 , R 3 and R 4 represents a linear or branched alkyl group having 1 to 18 carbon atoms, a cycloalkyl group, an allyl group, or a phenyl group. 1 , R 2 , R 3 and R 4 R may be a group containing a silica atom. 1 , R 2 , R 3 and R 4 When R is a cycloalkyl group or a phenyl group, some of the hydrogen atoms in the cycloalkyl ring or the benzene ring may be substituted with an alkyl group, such as a 4-methylcyclohexyl group or a 4-methylphenyl group. 1 , R 2 , R 3 and R 4may be the same or different groups. 1 , R 2 , R 3 and R 4 may be a linear or branched alkyl group, cycloalkyl group, allyl group, or phenyl group having 1 to 18 carbon atoms in which some of the hydrogen atoms have been substituted with a substituent such as a hydroxyl group, an amino group, or an alkoxy group.

[0046] Examples of the anion of X include a benzotriazole ion, a fluorine ion, a chloride ion, a bromide ion, an iodide ion, and BF4 - , PF6 - , PO2(OMe)3 - , PS2(OEt)2 - , (CO2Me)2PhSO3 - , CF3SO3 - , HSO4 - , (CF3SO2)2N - The anions exemplified here are preferred because they are easy to produce.

[0047] In the present invention, the compound having a preferred phosphonium group or ammonium group is preferably a phosphonium salt or ammonium salt represented by the following general formula (2). The phosphonium salt and ammonium salt having a silyl group represented by the general formula (2) have a hydrolyzable silyl group site. In the method for preparing silica particles having an ionic liquid fixed to the particle surface described below, the hydrolyzable site is hydrolyzed by an alkali in the same manner as alkoxysilane and directly bonds to the silica particles, which is preferable from the viewpoint of further improving adhesion to the metal coating. [ka] (In the formula, Q represents a P atom or a N atom. R 5 , R 6 and R 7 R represents a linear or branched alkyl group having 1 to 18 carbon atoms. 8 represents a linear or branched alkyl group having 1 to 5 carbon atoms; n represents an integer of 1 to 5; and X represents an anionic group.

[0048] Q in the formula (2) represents a P atom or a N atom, and is preferably a P atom. 5 ~R 7 R preferably represents a linear or branched alkyl group having 1 to 5 carbon atoms. 8 is preferably an alkyl group having 1 to 2 carbon atoms. The type of anion of X is not particularly limited, but may be, for example, a benzotriazole ion, a fluorine ion, a chloride ion, a bromide ion, an iodide ion, or a BF4 - , PF6 - , PO2(OMe)3 - , PS2(OEt)2 - , (CO2Me)2PhSO3 - , CF3SO3 - , HSO4 - , (CF3SO2)2N - The anions exemplified here are preferred because they are easy to produce.

[0049] The compound having a sulfonium group is preferably a compound represented by the following general formula (3). [ka] (In the formula, R 9 and R 10 represents an alkyl group having 1 to 5 carbon atoms. Z1 represents a phenylene group or an alkylene group having 1 to 5 carbon atoms. Z2 represents -(C=O)O-. R 11 represents an alkyl group having 1 to 20 carbon atoms. 1 indicates an anion.)

[0050] X in the general formula (3) 1 The type of anion is not particularly limited, but examples thereof include a fluorine ion, a chloride ion, a bromide ion, an iodide ion, a perchlorate ion, a hydrogen sulfate ion, a p-toluenesulfonate ion, and the like. The anions exemplified here are preferred in terms of ease of production.

[0051] The compound having a charged functional group selected from an amino group, a carboxyl group, a hydroxyl group, a sulfonic acid group, and a phosphate group is preferably one represented by the following general formula (4). R 12 Si(OR 13 )3(4)

[0052] In the general formula (4), R 12 R represents a hydrocarbon group having 1 to 8 carbon atoms and having 1 to 3 charged functional groups selected from amino groups, carboxyl groups, hydroxyl groups, sulfonic acid groups, and phosphate groups, an alicyclic hydrocarbon group having 1 to 3 charged functional groups selected from amino groups, carboxyl groups, hydroxyl groups, sulfonic acid groups, and phosphate groups, or an aromatic hydrocarbon group having 6 to 8 carbon atoms and having 1 to 3 charged functional groups selected from amino groups, carboxyl groups, hydroxyl groups, sulfonic acid groups, and phosphate groups. 13 represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 8 carbon atoms, an alicyclic hydrocarbon group having 3 to 8 carbon atoms, or an aromatic hydrocarbon group having 6 to 8 carbon atoms. 12 may be the same group or different groups.

[0053] The content of the compound having a charged functional group selected from a phosphonium group, an ammonium group, and a sulfonium group, or a condensate thereof (hereinafter, sometimes referred to as a "compound having functional group 1") in the insulating particles is preferably 0.001 to 50 mass%, preferably 0.1 to 30 mass%, and more preferably 0.1 to 10 mass%, from the viewpoint of improving adhesion to the metal coating.

[0054] The compound having the functional group 1 can be fixed to silica particles having an uneven surface (hereinafter, sometimes referred to as "uneven silica particles") by adding an alkali to a reaction raw material liquid containing the uneven silica particles, an alkoxysilane, a compound having the functional group 1, and a reaction solvent to hydrolyze the alkoxysilane, and then carrying out a surface treatment process to perform surface treatment on the silica particles.

[0055] The silica particles having projections and recesses and the compound having functional group 1 that can be used in the surface treatment step can be those described above.

[0056] Examples of alkoxysilanes used in the surface treatment process include tetraalkoxysilanes such as tetramethoxysilane and tetraethoxysilane, alkyltrialkoxysilanes such as methyltrimethoxysilane and methyltriethoxysilane, dialkyldialkoxysilanes such as dimethyldimethoxysilane and dimethyldiethoxysilane, and alkoxytrialkylsilanes such as hexyloxytrimethylsilane. The carbon chain length of the alkyl group in these alkoxysilanes is preferably 1 to 6. The carbon chain length of the alkoxy group is also preferably 1 to 6. Among these, tetraethoxysilane and tetramethoxysilane are preferred in terms of ease of handling in production. The alkoxysilanes may be used alone or in combination of two or more.

[0057] The reaction solvent used in the surface treatment step is one that dissolves alkoxysilane and a compound having a functional group 1. Examples of the reaction solvent used in the surface treatment step include lower alcohols such as methanol, ethanol, and isopropyl alcohol, and among these, methanol is particularly preferred from the viewpoint of high reaction efficiency. Alternatively, a mixed solvent of water and a lower alcohol may be used.

[0058] The content of the silica particles having an uneven surface in the reaction liquid is not particularly limited, but is preferably 1 to 80 mass%, and particularly preferably 3 to 50 mass%. When the content of the silica particles having an uneven surface in the reaction liquid is within the above range, the dispersion stability of the silica particles having an uneven surface to which the compound having the functional group 1 is fixed is increased.

[0059] The content of alkoxysilane in the reaction raw liquid is 0.05 to 1.5 mmol, preferably 0.08 to 1.05 mmol, per 1 g of the uneven silica particles. When the content of alkoxysilane in the reaction raw liquid is within the above range, the fixing rate of the compound having functional group 1 to the uneven silica particle surface is increased.

[0060] The content of the compound having functional group 1 in the reaction liquid is 0.001 ml or more, preferably 0.005 to 1.5 ml, and particularly 0.01 to 1.0 ml per gram of the uneven silica particles. When the content of the compound having functional group 1 in the reaction liquid is within the above range, the fixing rate of the compound having functional group 1 to the uneven silica particle surface is increased, and the adhesion with the metal coating is also increased.

[0061] In the surface treatment step, the alkali to be added to the reaction raw material liquid is not particularly limited as long as it is capable of hydrolyzing the alkoxysilane. For example, examples of the alkali include ammonium hydroxide, sodium hydroxide, and potassium hydroxide. Ammonium hydroxide is particularly preferred from the viewpoint of its high reactivity and ability to obtain the target product with high purity.

[0062] The amount of the alkali to be added to the reaction liquid is not particularly limited and may be appropriately selected.

[0063] The reaction temperature when the alkali is mixed into the reaction liquid to hydrolyze the alkoxysilane is 15 to 60° C., and preferably 20 to 35° C. When the reaction temperature is within the above range, the fixing rate of the compound having the functional group 1 to the uneven surface of the silica particles is increased, and the adhesion to the metal coating is also increased.

[0064] The reaction time is not particularly limited and may be appropriately selected, but is preferably 1 to 72 hours, and particularly preferably 1 to 24 hours.

[0065] After a surface treatment process in which an alkali is added to the reaction raw solution to hydrolyze the alkoxysilane, the solid matter is separated from the reaction solution by centrifugation or the like, and if necessary, the obtained solid matter is dispersed in a solvent and centrifuged again. This operation is repeated several times, and then the mixture is dried to obtain silica particles with irregularities on the particle surface on which a compound having functional group 1 is fixed.

[0066] In addition, after carrying out the surface treatment step, the reaction liquid may be heated under normal pressure or reduced pressure to a temperature at which the reaction solvent evaporates, and silica particles having an uneven surface and a compound having functional group 1 fixed to the particle surface may be recovered directly from the reaction liquid.

[0067] When a compound having a phosphonium group or an ammonium group represented by the general formula (3) is used as the compound having the functional group 1, the compound having a phosphonium group or an ammonium group has a hydrolyzable silyl group site, so that the surface treatment step may be carried out as is without using an alkoxysilane in the surface treatment step.

[0068] When a compound having a phosphonium group or an ammonium group represented by the general formula (3) is used as the compound having functional group 1, what is fixed to the uneven silica particles is a condensation product of the compound having a phosphonium group or an ammonium group represented by the general formula (3).

[0069] The content of a compound having a charged functional group selected from an amino group, a carboxyl group, a hydroxyl group, a sulfonic acid group, and a phosphate group, or a condensate thereof (hereinafter sometimes referred to as a "compound having functional group 2") in the insulating particles is 0.1 to 10 mass%, preferably 1 to 5 mass%, from the viewpoint of being able to uniformly coat the uneven surface of the silica particles.

[0070] The method of fixing the compound having the functional group 2 to the uneven silica particle surface can be carried out by a wet method or a dry method. When the compound having the functional group 2 is a compound represented by general formula (5) as a compound having a charged functional group, the compound having the functional group 2 fixed to the uneven silica particle surface may be a condensate thereof.

[0071] When the compound represented by the general formula (5) is used to fix silica particles having unevenness by a wet method, examples of the fixing method include: 1) immersing the silica particles having unevenness in a solvent containing a desired concentration of a compound having functional group 2, heating if necessary to promote the reaction between the silica particles having unevenness and the compound having functional group 2, and then spray drying together with the solvent or performing solid-liquid separation and drying; 2) adding a compound having functional group 2 to a dispersion containing silica particles having unevenness and a solvent, heating to 50 to 100°C to react, and then spray drying together with the solvent or performing solid-liquid separation and drying; and the like.

[0072] Solvents that can be used in the wet method include alcohols such as methanol, ethanol, and propanol, and mixed solvents of these alcohols with water.

[0073] When a compound having functional group 2 is used to perform a dry fixation treatment on uneven silica particles, examples of the fixation method include a method in which the compound having functional group 2 and the uneven silica particles are dry mixed using a mechanical means such as a Henschel mixer or an air flow grinder, or a method in which the compound having functional group 2 is diluted with a solvent, the diluted solution is mixed with the uneven silica particles, and the resulting mixture is heated and dried.

[0074] In the present invention, it is preferable to use insulating particles obtained by the wet method 2) above, from the viewpoint that monodispersed insulating particles are easily obtained and that coated particles with a high coverage are easily obtained.

[0075] In addition, R in the general formula (3) 12 In the case of a compound in which R is a sulfonic acid group, 12 A compound in which R is a mercapto group may be used, and a condensate of the compound may be fixed to the uneven silica particles as described above, and then the mercapto group may be converted to a sulfonic acid group by oxidation treatment with an oxidizing agent in a solvent.

[0076] Examples of the solvent that can be used include alcohols such as methanol, ethanol, and propanol, and mixed solvents of these alcohols with water.

[0077] Usable oxidizing agents include hydrogen peroxide, peracetic acid, and perbenzoic acid, and it is particularly preferable to use hydrogen peroxide from the viewpoint of obtaining a product of high purity. The amount of the oxidizing agent added is preferably 2 to 6 times by mole relative to the compound having the functional group 2, from the viewpoint of minimizing the amount of the residual oxidizing agent. The temperature for the oxidation reaction is not particularly limited, but is usually 5 to 100° C., and preferably 20 to 100° C., and the reaction time, although it depends on the reaction temperature, is usually 1 hour or more, and preferably 2 to 40 hours.

[0078] (Coated particles) The surface of the conductive particles may be coated with the insulating particles by a wet method or a dry method.

[0079] In the dry method, the mixture is prepared by a mechanical means that exerts a strong shearing force. Apparatuses that can be used in the dry method include a high-speed mixer, a super mixer, a turbosphere mixer, an Eirich mixer, a Henschel mixer, a hybridization system, a Nauta mixer, a ribbon blender, a jet mill, and a cosmoizer.

[0080] The wet method is a method in which insulating particles and conductive particles are brought into contact with each other through a solvent under stirring to cause the insulating particles to adhere to the surfaces of the conductive particles. Examples of the solvent that can be used include water, acetone, methanol, ethanol, and mixtures thereof.

[0081] When mixing the insulating particles and the conductive particles in a liquid medium, a dispersion liquid containing the insulating particles may be mixed with the conductive particles, a dispersion liquid containing the conductive particles may be mixed with the insulating fine particles, or the insulating particles and the conductive particles may be separately put into a solvent, or a dispersion medium containing the insulating particles may be mixed with a dispersion medium containing the conductive particles. In the dispersion liquid containing the conductive particles and the insulating particles, the conductive particles are preferably contained in an amount of 100 ppm or more and 100,000 ppm or less by mass, and more preferably 500 ppm or more and 80,000 ppm or less.

[0082] In a dispersion liquid containing conductive particles and insulating particles, the insulating particles are contained in an amount of preferably 10 ppm or more and 50,000 ppm or less, and more preferably 250 ppm or more and 10,000 ppm or less, based on mass.

[0083] In the dispersion liquid after mixing the conductive particles, the time for the insulating particles to adhere to the conductive particles is preferably 0.1 hours or more and 24 hours or less. During this time, it is preferable to stir the dispersion liquid. Next, the solid content of the dispersion liquid is washed and dried as necessary to obtain coated particles in which the insulating particles are adhered to the surfaces of the conductive particles.

[0084] The temperature at which the insulating particles and the conductive particles are brought into contact is not particularly limited, but is 5 to 100° C., preferably 10 to 50° C., and is also sufficient at around room temperature (25° C.) The coated particles of the present invention can be obtained by recovering the solid content from the solvent by a conventional method, and washing and drying as necessary.

[0085] When insulating particles and conductive particles are mixed in a solvent, the dispersion liquid consisting of these particles and the solvent may contain an inorganic salt, an organic salt or an organic acid, if necessary, in order to increase the coverage of the insulating particles. As the inorganic salt, organic salt or organic acid, one that dissociates an anion is preferably used, and the anion is, for example, Cl. - , F - , Br - , I - , SO4 2- , CO32- , NO3 - , COO - , R.C.O.O. - (R is an organic group), etc. are suitable. As inorganic salts, for example, NaCl, KCl, LiCl, MgCl2, BaCl2, NaF, KF, LiF, MgF2, BaF2, NaBr, KBr, LiBr, MgBr2, BaBr2, NaI, KI, LiI, MgI2, BaI2, Na2SO4, K2SO4, Li2SO4, MgSO4, Na2CO3, NaHCO3, K2CO3, KHCO3, Li2CO3, LiHCO3, MgCO3, NaNO3, KNO3, LiNO3, MgNO3, BaNO3, etc. can be used. As organic salts, sodium succinate, sodium oxalate, sodium acetate, sodium citrate, sodium malonate, sodium tartrate, sodium fumarate, sodium maleate, etc. can be used. As the organic acid, an amino acid such as glycine, succinic acid, oxalic acid, acetic acid, citric acid, tartaric acid, malonic acid, fumaric acid, maleic acid, etc. can be used.

[0086] The preferred concentrations of inorganic salts, organic salts and organic acids vary depending on the extent to which the insulating particles occupy a covering area of ​​the conductive particle surface area, but in a dispersion containing insulating particles and conductive particles, a concentration of, for example, 5 mmol / L to 100 mmol / L is preferred because it is easy to obtain covered particles having a suitable coverage and a single layer of insulating particles. From this viewpoint, the concentrations of inorganic salts, organic salts and organic acids in the dispersion are more preferably 7 mmol / L to 90 mmol / L, and particularly preferably 10 mmol / L to 80 mmol / L.

[0087] Furthermore, when an inorganic salt, an organic salt, or an organic acid is added to a dispersion liquid containing conductive particles and insulating particles, it is generally preferable to set the temperature at 20° C. or higher and 100° C. or lower in order to easily obtain coated particles of consistent quality, and it is particularly preferable to set the temperature at 40° C. or higher and 90° C. or lower. This range is preferable because it is easy to obtain a suitable contact area between the insulating particles and the conductive particles.

[0088] Alternatively, the coated particles of the present invention may be obtained by a method comprising a first step of reacting a compound having, in the same molecule, a functional group (A) reactive with the metal coating in the conductive particle and a functional group (B) reactive with a charged functional group in a compound containing a charged functional group contained in an insulating particle (hereinafter sometimes referred to as a "reactive compound") with the metal coating of the conductive particle, followed by a second step of reacting with the insulating particle.

[0089] Examples of the functional group (A) include a silane group, a silanol group, a carboxyl group, an amino group, an ammonium group, a nitro group, a hydroxyl group, a carbonyl group, a thiol group, a sulfonic acid group, a sulfonium group, a boric acid group, an oxazoline group, a pyrrolidone group, a phosphate group, and a nitrile group.

[0090] The functional group (B) varies depending on the type of compound or condensate thereof that contains a functional group having an electric charge to be fixed to the uneven silica particle. For example, in the case of a compound containing a functional group having an electric charge, a mercapto group may be used as the compound. Examples of the functional group (B) include an epoxy group, an amino group, a halide group, a hydroxyl group, a carboxylic acid halide group, a carboxylic acid anhydride group, a group having a carbon-carbon double bond, a cyclic ether group, a cyclic thioether group, an isocyanato group, and an isothiocyanato group.

[0091] In addition, in the case of a compound having a sulfonic acid group as a compound containing a functional group having a charge, examples of the functional group (B) include an epoxy group, an amino group, a hydroxyl group, an isocyanate group, an oxazoline group, a carbodiimide group, and a halogen group.

[0092] In addition, in the case of a compound having a phosphonium group or an ammonium group as a compound containing a functional group having a charge, examples of the functional group (B) include an amino group, a halide group, a hydroxyl group, a carboxyl group, a sulfonic acid group, a phosphonic acid group, and a phosphate group.

[0093] The first step can be carried out by a known method, for example, the methods described in WO2003 / 025955 pamphlet, JP-A 2001-342377, JP-A 2003-26813, and the like.

[0094] The second step can be carried out in a wet or dry manner.

[0095] In the dry method, the mixture is prepared by a mechanical means that exerts a strong shearing force. Apparatuses that can be used in the dry method include a high-speed mixer, a super mixer, a turbosphere mixer, an Eirich mixer, a Henschel mixer, a hybridization system, a Nauta mixer, a ribbon blender, a jet mill, and a cosmoizer.

[0096] The wet method is a method in which insulating particles and conductive particles coated with a reactive compound are brought into contact with each other through a solvent under stirring, and the insulating particles are attached to the surfaces of the conductive particles coated with the reactive compound. Examples of solvents that can be used include water, acetone, methanol, ethanol, and mixed solvents thereof. The temperature at which the insulating particles and the conductive particles coated with a reactive compound are brought into contact is not particularly limited, but is 5 to 100°C, preferably 10 to 50°C, and is also sufficient even at around room temperature (25°C). The solid content is recovered from the solvent by a conventional method, and washed and dried as necessary to obtain the coated particles of the present invention. can be obtained.

[0097] The coated particles according to the present invention preferably have a coverage rate of insulating particles of 30% or more, preferably 30 to 100%, and particularly preferably 30 to 80%, from the viewpoint of achieving excellent electrical reliability when the coated particles are used to electrically connect upper and lower electrodes.

[0098] The coverage rate was calculated by counting the number n of insulating particles attached to the conductive particles using an SEM and using the following formula: The coverage rate used for evaluation is the average value of 20 coated particles. Coverage rate (%) = (n / N) x 100 N: The number of insulating particles when the insulating particles are arranged in close packing on the surface of a conductive particle N=4π(R+r) 2 / 2√3r 2 (R: radius of conductive particle (nm), r: radius of insulating particle (nm))

[0099] In addition, the coated particles according to the present invention may be conductive particles that have been surface-treated with a hydrophobizing agent. The presence of a hydrophobizing agent on the surface of the conductive particles provides excellent affinity with the insulating particles, and the coverage of the insulating particles can be further increased. Examples of the hydrophobizing agent include benzotriazole-based compounds, titanate-based coupling agents, higher fatty acids and their derivatives, phosphates and phosphites, etc. These may be used alone or in combination of two or more kinds, if necessary.

[0100] In this case, the insulating particles may be bonded to the conductive particles 1) via a hydrophobizing agent present on the particle surface of the conductive particles, or 2) directly to the particle surface of the conductive particles without the hydrophobizing agent, or may be bonded in a mixture of 1) and 2).

[0101] The benzotriazole compound is preferably one represented by the following general formula (4). [ka] (In the formula, A1 and A2 are the same or different and represent an alkyl group, an aryl group, a halogen atom, a hydroxyl group, an amino group, or a carboxyl group, and p1 and q1 are the same or different and represent an integer of 0 to 2.) A1 and A2 in the general formula (4) represent an alkyl group, an aryl group, a halogen atom, a hydroxyl group, an amino group, or a carboxyl group. The alkyl group is preferably an alkyl group having 1 to 5 carbon atoms, such as a methyl group, an ethyl group, a propyl group, or a butyl group. The aryl group is preferably a phenyl group, a tolyl group, a xylyl group, or a naphthyl group. The halogen atom includes chlorine, bromine, and iodine. p1 and q1 in the general formula (4) represent integers of 0 to 2, which may be the same or different. A1 and A2 may be the same or different groups.

[0102] Specific preferred examples of the benzotriazole-based compound represented by the general formula (4) include benzotriazole, 4-methylbenzotriazole, 5-methylbenzotriazole, 4-ethylbenzotriazole, 5-ethylbenzotriazole, 4,5-dimethylbenzotriazole, 4,6-dimethylbenzotriazole, 5,6-dimethylbenzotriazole, 4,5-diethylbenzotriazole, 4,6-diethylbenzotriazole, 5,6-diethylbenzotriazole, 4-phenylbenzotriazole, 5-phenylbenzotriazole, 4-chlorobenzotriazole, 5-chlorobenzotriazole, 4-carboxybenzotriazole, 5-carboxybenzotriazole, 4,5-dicarboxybenzotriazole, and 4,6-dicarboxybenzotriazole.

[0103] Examples of titanate-based coupling agents include those represented by the following formula (i) or formula (ii). (B 1 O)Ti(OB 2 )(OB 3 )(OB 4 ) (i) (In the formula, B 1 is an alkyl group, B 2 ~B 4are each a group selected from an alkyl group, an alkyl group in which a methylene group other than the terminal group is substituted with an oxygen atom, an alkenyl group, an alkenyl group in which a methylene group other than the terminal group is substituted with an oxygen atom, an alkanoyl group, a dialkylpyrophosphate group, and an alkylbenzenesulfonyl group, provided that B 2 ~B 4 At least one of the above is an alkanoyl group, a dialkylpyrophosphate group, or an alkylbenzenesulfonyl group. 1 and B 2 may join together to form a ring.)

[0104] (B 5 O)Ti(OB 6 )(OB 7 )(OB 8 )·[P(OB 9 )2OH]2(ii) (In the formula, B 5 ~B 8 are respectively an alkyl group, an alkyl group in which a methylene group other than the terminal group is substituted with an oxygen atom, an alkenyl group, or an alkenyl group in which a methylene group other than the terminal group is substituted with an oxygen atom. 9 is an alkyl group. In the above formula (i), B 1 ~B 4 Two or three of the groups may be the same; B 1 ~B 4 In the compound represented by formula (ii), B 5 ~B 8 Two or three of the groups may be the same; B 5 ~B 8 may all be different. 9 In the compound represented by formula (i), the number of alkanoyl groups, dialkylpyrophosphate groups or alkylbenzenesulfonyl groups is preferably 1 to 3, more preferably 2 to 3, and particularly preferably 3.

[0105] Examples of the alkyl group mentioned above include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, n-pentyl group, isopentyl group, 2-methylbutyl group, 1-methylbutyl group, n-hexyl group, isohexyl group, 3-methylpentyl group, 2-methylpentyl group, 1-methylpentyl group, heptyl group, octyl group, isooctyl group, 2-ethylhexyl group, 3,7-dimethyloctyl group, nonyl group, decyl group, undecyl group, dodecyl group, lauryl group, tetradecyl group, hexadecyl group, octadecyl group (including stearyl group), nonadecyl group, eicosyl group, triacontyl group, and tetracontyl group. Examples of the alkenyl group include groups in which one or more carbon-carbon single bonds of the above alkyl groups are changed to carbon-carbon double bonds.

[0106] The group in which a methylene group other than the terminal in an alkyl group is replaced with an oxygen atom is not an alkoxy group, but includes a group in which methylene groups in an alkyl group are interrupted by an oxygen atom. The same groups can be mentioned for a group in which a methylene group other than the terminal in an alkenyl group is replaced with an oxygen atom.

[0107] B 1 ~B 4 , B 5 ~B 8 The number of carbon atoms in the alkyl group represented by the formula (I), the group in which a methylene group other than the terminal in the alkyl group is substituted with an oxygen atom, the alkenyl group, and the group in which a methylene group other than the terminal in the alkenyl group is substituted with an oxygen atom is preferably 3 to 40, and more preferably 3 to 32. 2 ~B 4 The alkanoyl group represented by the formula (I) is preferably one having 2 to 40 carbon atoms. 2 ~B 4 The alkyl group of the dialkylpyrophosphate group represented by the formula (I) preferably has 3 to 40 carbon atoms. 2 ~B 4 The alkyl group of the alkylbenzenesulfonyl group represented by the formula (I) is preferably one having 3 to 40 carbon atoms. 9The alkyl group represented by the following formula (I) is preferably one having 3 to 40 carbon atoms.

[0108] B 1 and B 2 Examples of the ring formed by combining with the oxygen atom and titanium atom in formula (i) include -CH2-CH2- or -CH2-COO-.

[0109] Each group represented by the above formula (i) or (ii) may be substituted with a substituent, such as a halogen atom, an epoxy group, an amino group, a vinyl group, an acryl group, an isocyanate group, or a mercapto group.

[0110] Specific examples of titanate-based coupling agents used in the present invention include isopropyl triisostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraisopropyl(dioctyl phosphite) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, and the like. These may be used alone or in combination of two or more. These titanate coupling agents are commercially available, for example, from Ajinomoto Fine-Techno Co., Ltd.

[0111] The higher fatty acid is preferably a saturated or unsaturated linear or branched mono- or polycarboxylic acid, more preferably a saturated or unsaturated linear or branched monocarboxylic acid, and even more preferably a saturated or unsaturated linear monocarboxylic acid. The fatty acid preferably has 7 or more carbon atoms. The derivative refers to a salt or amide of the fatty acid.

[0112] The fatty acid or its derivative used in the present invention has a carbon number of the fatty acid of preferably 7 to 23, more preferably 10 to 20. Examples of such fatty acids or their derivatives include saturated fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, and stearic acid, unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, and arachidonic acid, and metal salts or amides thereof. Examples of metal salts of fatty acids include salts of alkali metals, alkaline earth metals, transition metals such as Zr, Cr, Mn, Fe, Co, Ni, Cu, and Ag, and metals other than transition metals such as Al and Zn, and are preferably polyvalent metal salts such as Al, Zn, W, and V. The fatty acid metal salt may be mono-, di-, tri-, or tetra-form depending on the valence of the metal. The fatty acid metal salt may be any combination of these.

[0113] As the phosphate ester and the phosphite ester, those having an alkyl group having 6 to 22 carbon atoms are preferably used. Examples of phosphate esters include hexyl phosphate, heptyl phosphate, monooctyl phosphate, monononyl phosphate, monodecyl phosphate, monoundecyl phosphate, monododecyl phosphate, monotridecyl phosphate, monotetradecyl phosphate, and monopentadecyl phosphate. Examples of phosphite esters include hexyl phosphite, heptyl phosphite, monooctyl phosphite, monononyl phosphite, monodecyl phosphite, monoundecyl phosphite, monododecyl phosphite, monotridecyl phosphite, monotetradecyl phosphite, and monopentadecyl phosphite.

[0114] In the present invention, the hydrophobizing agent is preferably a triazole-based compound or a titanate-based coupling agent, in that it has excellent affinity with the insulating particles and is highly effective in increasing the coverage of the insulating particles, and in particular, benzotriazole, 4-carboxybenzotriazole, isopropyl triisostearoyl titanate, and tetraisopropyl (dioctyl phosphite) titanate are particularly preferred.

[0115] In the present invention, the hydrophobizing agent may be present on the surface of the conductive particle, and in that case, the hydrophobizing agent may be present on the entire surface of the conductive particle or only on a part of the surface. The hydrophobizing agent may also form a layer that covers a part or the entire surface of the conductive particle.

[0116] The method for surface-treating the conductive particles with a hydrophobizing agent is not particularly limited, and any known method can be used, such as a method in which the conductive particles and the hydrophobizing agent are mixed in a solvent.

[0117] The solvent may be water or an organic solvent, or may be a mixed solvent of water and an organic solvent. Examples of the organic solvent include toluene, methanol, ethanol, propanol, butanol, isobutyl alcohol, acetone, methyl ethyl ketone, tetrahydrofuran, acetonitrile, N-methylpyrrolidone, and dimethylformamide. In a dispersion liquid in which conductive particles and a hydrophobizing agent are added to a solvent, the concentration of the hydrophobizing agent is 0.01 to 20% by mass. The concentration of the conductive particles in this dispersion liquid is 1 to 50% by mass.

[0118] The dispersion liquid after the treatment is filtered and, if necessary, dried to obtain conductive particles having a hydrophobizing agent on the surface thereof. In addition, as a method for coating the insulating particles on the particle surfaces of the conductive particles that have been surface-treated with a hydrophobizing agent, a method similar to the method for coating the insulating particles on the particle surfaces of the conductive particles described above can be used.

[0119] The coated particles of the present invention, taking advantage of the insulating properties between coated particles and the connectivity between opposing electrodes, are suitably used, for example, as an anisotropic conductive film (ACF), a heat seal connector (HSC), a conductive material for connecting electrodes of a liquid crystal display panel to a circuit board of a driving LSI chip, etc. In particular, they are suitably used as a conductive filler for conductive adhesives.

[0120] The conductive adhesive is preferably used as an anisotropic conductive adhesive that is disposed between two substrates on which a conductive base material is formed, and that adheres the conductive base material to conduct electricity by heating and pressurization. This anisotropic conductive adhesive contains the coated particles of the present invention and an adhesive resin. The adhesive resin can be used without any particular limitation as long as it is insulating and is used as an adhesive resin. It may be either a thermoplastic resin or a thermosetting resin, and it is preferable that the adhesive performance is expressed by heating. Such adhesive resins include, for example, a thermoplastic type, a thermosetting type, an ultraviolet curing type, and the like. In addition, there are so-called semi-thermosetting types that show intermediate properties between the thermoplastic type and the thermosetting type, and composite types of a thermosetting type and an ultraviolet curing type. These adhesive resins can be appropriately selected according to the surface characteristics of the circuit board or the like to be adhered and the form of use. In particular, an adhesive resin that includes a thermosetting resin is preferable because it has excellent material strength after adhesion.

[0121] Specific examples of adhesive resins include those prepared using as the main component one or a combination of two or more selected from ethylene-vinyl acetate copolymer, carboxyl-modified ethylene-vinyl acetate copolymer, ethylene-isobutyl acrylate copolymer, polyamide, polyimide, polyester, polyvinyl ether, polyvinyl butyral, polyurethane, SBS block copolymer, carboxyl-modified SBS copolymer, SIS copolymer, SEBS copolymer, maleic acid-modified SEBS copolymer, polybutadiene rubber, chloroprene rubber, carboxyl-modified chloroprene rubber, styrene-butadiene rubber, isobutylene-isoprene copolymer, acrylonitrile-butadiene rubber (hereinafter referred to as NBR), carboxyl-modified NBR, amine-modified NBR, epoxy resin, epoxy ester resin, acrylic resin, phenol resin, silicone resin, etc. Among these, styrene-butadiene rubber and SEBS are preferable as thermoplastic resins because they have excellent reworkability. As thermosetting resins, epoxy resins are preferable. Of these, epoxy resins are most preferred because of their advantages of high adhesive strength, excellent heat resistance and electrical insulation, low melt viscosity, and ability to connect at low pressure.

[0122] As the epoxy resin, any commonly used epoxy resin can be used as long as it is a polyhydric epoxy resin having two or more epoxy groups in one molecule. Specific examples include novolac resins such as phenol novolac and cresol novolac, polyhydric phenols such as bisphenol A, bisphenol F, bisphenol AD, resorcin, and bishydroxydiphenyl ether, polyhydric alcohols such as ethylene glycol, neopentyl glycol, glycerin, trimethylolpropane, and polypropylene glycol, polyamino compounds such as ethylenediamine, triethylenetetramine, and aniline, and polyvalent carboxy compounds such as adipic acid, phthalic acid, and isophthalic acid, and glycidyl-type epoxy resins obtained by reacting epichlorohydrin or 2-methylepichlorohydrin. In addition, aliphatic and alicyclic epoxy resins such as dicyclopentadiene epoxide and butadiene dimer diepoxide can be mentioned. These can be used alone or in combination of two or more.

[0123] From the viewpoint of preventing ion migration, it is preferable to use high-purity adhesive resins in which impurity ions (Na, Cl, etc.) and hydrolyzable chlorine are reduced as the various adhesive resins mentioned above.

[0124] The amount of conductive particles used in the anisotropic conductive adhesive is usually 0.1 to 30 parts by mass, preferably 0.5 to 25 parts by mass, and more preferably 1 to 20 parts by mass, per 100 parts by mass of the adhesive resin component. By keeping the amount of conductive particles within this range, increases in connection resistance and melt viscosity are suppressed, connection reliability is improved, and connection anisotropy can be sufficiently ensured.

[0125] In addition to the conductive particles and adhesive resin described above, the anisotropic conductive adhesive may contain additives known in the art. The amount of the additives may be within a range known in the art. Examples of other additives include tackifiers, reactive assistants, epoxy resin curing agents, metal oxides, photoinitiators, sensitizers, curing agents, vulcanizing agents, anti-degradation agents, heat resistance additives, thermal conductivity improvers, softeners, colorants, various coupling agents, or metal deactivators.

[0126] Examples of tackifiers include rosin, rosin derivatives, terpene resins, terpene phenol resins, petroleum resins, coumarone-indene resins, styrene resins, isoprene resins, alkylphenol resins, and xylene resins. Examples of reactive auxiliaries, i.e., crosslinking agents, include polyols, isocyanates, melamine resins, urea resins, utropines, amines, acid anhydrides, and peroxides. As epoxy resin curing agents, any agent having two or more active hydrogens per minute can be used without any particular limitations. Specific examples include polyamino compounds such as diethylenetriamine, triethylenetetramine, metaphenylenediamine, dicyandiamide, and polyamidoamine; organic acid anhydrides such as phthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and pyromellitic anhydride; and novolac resins such as phenol novolac and cresol novolac. These can be used alone or in combination of two or more. If necessary, a latent curing agent may be used. Examples of usable latent curing agents include imidazoles, hydrazides, boron trifluoride-amine complexes, sulfonium salts, aminimides, polyamine salts, dicyandiamide, and modified products thereof. These can be used alone or in combination of two or more.

[0127] The anisotropic conductive adhesive is manufactured using a manufacturing device commonly used in the technical field. For example, the adhesive resin is mixed with conductive particles and a curing agent or various additives as necessary, and is manufactured by mixing in an organic solvent when the adhesive resin is a thermosetting resin, or by melt-kneading at a temperature above the softening point of the adhesive resin, preferably about 50 to 150°C, when the adhesive resin is a thermoplastic resin. The anisotropic conductive adhesive thus obtained may be applied as a coating or in the form of a film. EXAMPLES

[0128] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0129] <Preparation of dispersion containing uneven silica particles> 117g of JIS No. 3 sodium silicate (SiO2: 29.0%, Na2O: 9.7%, H2O: 61.3%) was added to 733g of deionized water and mixed uniformly to prepare diluted sodium silicate containing 4.0% SiO2. This diluted sodium silicate was passed through a column of H-type strongly acidic cation exchange resin that had been regenerated with hydrochloric acid in advance to dealkalize it, obtaining 900g of active silicic acid with a silica concentration of 3.5% and a pH of 2.9. 217g of large-particle colloidal silica with a silica concentration of 41% and a particle size of 80nm was mixed with 2783g of deionized water to obtain diluted large-particle colloidal silica with a silica concentration of 3%. Separately, 20g of small-particle colloidal silica with a silica concentration of 15% and a particle size of 7nm was mixed with 280g of deionized water to obtain diluted small-particle colloidal silica with a silica concentration of 1%. The diluted large-particle colloidal silica was added to the diluted small-particle colloidal silica under stirring. Next, 26g of a solution of 2.6g of aluminum chloride hexahydrate (AlCl3·6H2O) dissolved in 23.4g of deionized water was mixed. The entire solution was mixed and stirred for 30 minutes, then heated to 98°C and held at this temperature for 1 hour, after which 900g of active silicic acid and 81g of 1% caustic soda were added over 1.6 hours. The temperature was kept at 98°C during the addition, and after the addition was completed, the mixture was heated to 98°C and kept at this temperature for 1 hour, and then allowed to cool to 50°C. The obtained colloidal silica dispersion was subjected to pressure filtration by pump circulation using a hollow fiber ultrafiltration membrane (Microza UF module SIP-1013, manufactured by Asahi Kasei Corporation) with a molecular weight cutoff of 6000, to obtain about 400g of uneven silica with a silica concentration of 30%. TEM images of this colloidal silica showed that the particle surfaces were uneven, and the average particle size determined from the TEM was 99 nm. The average particle size measured by TEM was determined by randomly selecting 50 particles, measuring their particle sizes, and averaging the measurements. FIG. 1 shows a TEM image of the resulting silica particles with irregularities.

[0130] <Preparation of insulating particle samples> (Insulating Particles 1) In a reaction vessel, 45 g of methanol was added to 58.2 g of the dispersion containing the uneven silica particles obtained above (SiO2: 30 mass%, water: 70 mass%) to obtain a dispersion. Next, 0.15 g of 3-mercaptopropyltrimethoxysilane was added to the dispersion while stirring, and the mixture was stirred for 20 minutes. Then, the temperature of the reaction vessel was raised to 60° C., and the mixture was stirred for 3 hours to complete the reaction. After the reaction was completed, the solids were collected by filtration, washed with methanol, and dried at 120°C under vacuum for 12 hours to obtain insulating particles 1 in which the surfaces of the uneven silica particles were surface-treated with 3-mercaptopropyltrimethoxysilane.

[0131] (Insulating particles 2) In a reaction vessel, 45 g of methanol was added to 58.2 g of the dispersion containing the uneven silica particles obtained above (SiO2: 30 mass%, water: 70 mass%) to obtain a dispersion. Next, 0.15 g of 3-mercaptopropyltrimethoxysilane was added to the dispersion while stirring, and the mixture was stirred for 20 minutes. Then, the temperature of the reaction vessel was raised to 60° C., and the mixture was stirred for 3 hours to complete the reaction. Next, the reaction solution was cooled to room temperature (25° C.), and then 0.25 g of 31% by weight hydrogen peroxide solution was added and the reaction was carried out for 5 hours while boiling. After the reaction was completed, the solid matter was recovered by filtration, washed with methanol, and dried at 120°C under vacuum for 12 hours to obtain uneven silica particles in which a condensate of a silane coupling agent having a sulfonic acid group was fixed to the particle surface via a chemical bond, which was designated as insulating particles 2.

[0132] (Insulating particles 3) As a compound containing a functional group having a charge, the following compound (a) was used. [ka] 200 ml of methanol was placed in a container, and then 0.5 ml of compound (a) and 58.2 g of the dispersion containing the uneven silica particles obtained above (SiO2: 30% by mass, water: 70% by mass) were added to obtain a dispersion. Then, 23 mmol of tetraethoxysilane was added and mixed by stirring. Next, 5 ml of 25% ammonium water was added while stirring thoroughly, and the mixture was stirred at 30°C overnight, and then concentrated. After concentration, methanol was added to the solids, and the mixture was stirred overnight to disperse the solids, and centrifuged. This operation was repeated twice to purify the solids after concentration. The purified solids were vacuum-dried in a reduced-pressure desiccator to obtain uneven silica particles with the reaction residue of compound (a) fixed thereto. Furthermore, elemental analysis of the obtained silica particles having irregularities and having the reaction residue of compound (a) fixed thereto revealed that the content of the reaction residue of compound (a) was 3.0 mass %. These were designated insulating particles 3.

[0133] (Insulating Particles 4) As a compound containing a functional group having a charge, the following compound (b) was used. [ka] 200 ml of methanol was placed in a container, and then 0.5 ml of compound (b) and 58.2 g of the dispersion containing the uneven silica particles obtained above (SiO2: 30% by mass, water: 70% by mass) were added to obtain a dispersion. Then, 23 mmol of tetraethoxysilane was added and mixed by stirring. Next, 5 ml of 25% ammonium water was added while stirring thoroughly, and the reaction was carried out by stirring at 25°C for 5 hours. After the reaction was completed, the reaction solution was distilled under reduced pressure at 50°C to remove the solvent, and uneven silica particles with the reaction residue of compound (b) fixed were obtained. In addition, elemental analysis was performed on the obtained uneven silica particles with the reaction residue of compound (b) fixed, and the content of the reaction residue of compound (b) was 2.0% by mass.

[0134] (Insulating Particles 5) Except for not adding tetraethoxysilane, silica particles with irregularities having reaction residues of compound (b) fixed thereto were obtained in the same manner as insulating particles 4. Furthermore, elemental analysis was performed on the obtained silica particles with irregularities having reaction residues of compound (b) fixed thereto, and the content of reaction residues of compound (b) was found to be 2.2 mass%.

[0135] (Insulating Particles 6) 100 ml of pure water was added to a 200 ml four-neck flask equipped with a stirring blade. Then, 30.00 mmol of styrene monomer, 0.03 mmol of 4-(vinylbenzyl)triethylammonium chloride, and 0.50 mmol of 2,2'-azobis(2-methylpropionamidine)dihydrochloride as a polymerization initiator were added. Nitrogen was aerated for 15 minutes to expel dissolved oxygen, and the temperature was raised to 60°C and maintained for 6 hours to allow the polymerization reaction to proceed. The dispersion of fine particles after polymerization was passed through a SUS sieve with a mesh size of 150 μm to remove aggregates. The dispersion from which the aggregates had been removed was centrifuged to settle the fine particles, and the supernatant was removed. The solid matter thus obtained was washed with pure water to obtain spherical microparticles of poly(styrene / 4-(vinylbenzyl)triethylammonium chloride). The average particle size of the obtained microparticles was 272 nm.

[0136] (Insulating Particles 7) Insulating particles 7 were obtained in which the surfaces of the silica particles were surface-treated with 3-mercaptopropyltrimethoxysilane in the same manner as insulating particles 1, except that a dispersion containing commercially available colloidal silica (SiO2: 30 mass%, water: 70 mass%) was used instead of a dispersion containing uneven silica particles (SiO2: 30 mass%, water: 70 mass%). TEM images of this colloidal silica showed that the colloidal silica was spherical and had an average particle size of 95 nm. The average particle size measured by TEM was determined by randomly selecting 50 particles, measuring their particle sizes, and averaging the measurements.

[0137] (Insulating particles 8) Silica particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the particle surface via a chemical bond were obtained in the same manner as for insulating particles 2, except that a dispersion containing commercially available colloidal silica (SiO2: 30% by mass, water: 70% by mass) was used instead of a dispersion containing uneven silica particles (SiO2: 30% by mass, water: 70% by mass), and these were designated as insulating particles 8. TEM images of this colloidal silica showed that the colloidal silica was spherical and had an average particle size of 95 nm. The average particle size measured by TEM was determined by randomly selecting 50 particles, measuring their particle sizes, and averaging the measurements.

[0138] <Preparation of conductive particle samples> The conductive particles used were the following commercially available conductive particles. The average particle diameter of the conductive particles was determined by randomly extracting 200 particles from a scanning electron microscope (SEM) photograph (magnification 100,000 times), measuring their particle diameters, and averaging the results.

[0139] (Conductive Particles 1) Ni-plated particles (manufactured by Nippon Chemical Industry Co., Ltd.) with an average particle size of 3 μm were prepared, in which the surface of spherical resin particles had a nickel coating with a thickness of 0.125 μm. The resin particles were made of a crosslinkable acrylic resin and had a glass transition temperature of 120° C. The average particle size was determined by measuring the particle sizes of randomly selected particles from a scanning electron microscope (SEM) photograph (magnification: 100,000 times), and averaging the measured values.

[0140] (Conductive particles 2) Ni-plated particles (manufactured by Nippon Chemical Industry Co., Ltd.) with an average particle diameter of 3 μm were prepared, which had 1,030 protrusions on the surface of spherical resin particles, with an average height of 0.1 μm, an average base length of 0.197 μm, and an aspect ratio of 0.5, and a nickel coating with a thickness of 0.125 μm. The resin particles were made of a crosslinked acrylic resin and had a glass transition temperature of 120° C. The average particle diameter was measured in the same manner as for the conductive particles 1.

[0141] (Conductive particles 3) Gold-plated particles (manufactured by Nippon Chemical Industry Co., Ltd.) with an average particle size of 4.6 μm and a conductive gold-nickel layer on the surface of spherical resin particles were used. The resin particles were made of crosslinkable acrylic resin and had a glass transition temperature of 120° C. The average particle size was determined by measuring the particle sizes of randomly selected particles from a scanning electron microscope (SEM) photograph (magnification: 100,000 times), and averaging the measured values.

[0142] {Examples 1-2 and Reference Examples 1-2} An insulating particle dispersion liquid was prepared by adding pure water to make the total volume 20 ml, so that the solid content concentration of the insulating particles obtained above was 10,000 ppm. 50 mg of each conductive particle sample was added to this dispersion liquid, and the mixture was stirred at room temperature (25°C) for 15 hours. Next, the solid content was separated from the stirred dispersion using a membrane filter with 10 μm openings, washed with water, and dried to obtain a coated particle sample.

[0143] {Examples 3 to 9} 100 ml of pure water was added to 5.0 g of the conductive particles, and the mixture was stirred to obtain a dispersion of conductive particles. The insulating particles and Na2SO4 prepared above were added to this dispersion, and the mixture was stirred at 40°C for 30 minutes. After the insulating particles and Na2SO4 were added, the solid concentration of the insulating particles in the dispersion was 10,000 ppm by mass, and the concentration of Na2SO4 was 5 mmol / l. After removing the supernatant, the mixture was washed with pure water and then vacuum dried at 50°C to obtain a coated particle sample.

[0144] {Comparative Example 1} The insulating particle dispersion liquid was prepared by adding pure water and NaCl to the insulating particle 6 obtained above so that the solid content concentration was 10,000 ppm, the NaCl concentration was 25 mmol, and the total volume was 20 ml. 50 mg of the conductive particle sample 1 was added to this dispersion liquid, and the mixture was stirred at room temperature (25° C.) for 15 hours. Next, the solid content was separated from the stirred dispersion using a membrane filter with 10 μm openings, washed with water, and dried to obtain a coated particle sample.

[0145] (Coverage evaluation) The difference in coverage when insulating particles are coated on conductive particles was evaluated from the coated particles obtained in the examples and comparative examples. The results are shown in Table 1. The coverage was determined by the following method.

[0146] <Method of measuring coverage> The number N of insulating particles when the insulating particles are arranged in close packing on the surface of a conductive particle was calculated using the following formula. N=4π(R+r) 2 / 2√3r 2 (R: radius of conductive particle (nm), r: radius of insulating particle (nm)) The number n of insulating particles attached to the conductive particles was counted using an SEM, and the coverage rate was calculated using the following formula. The results are shown in Table 1. Coverage rate (%) = (n / N) x 100 The coverage used in the evaluation was the average value for 20 conductive particles.

[0147] (Evaluation of adhesion) 1 g of the coated particles obtained in the examples and comparative examples was added to 100 mL of pure water, and ultrasonic treatment was performed for 2 minutes using an ultrasonic device (VS-D100, manufactured by VELVO-CLEAR) at an oscillation frequency of 24 kHz to obtain coated particles. The coverage was calculated in the same manner as in the evaluation of the coverage, and the adhesion was evaluated by calculating the degree of adhesion using the following formula, and the results are shown in Table 1. The higher the adhesion value, the less the insulating particles fell off due to ultrasonic treatment, which means that the adhesion between the conductive particles and the insulating particles is high. Adhesion rate (%) = (coverage rate after ultrasonic treatment / coverage rate before ultrasonic treatment) x 100

[0148] [Table 1]

[0149] Example 10 100 ml of pure water was added to the conductive particles 2 (5 g) obtained above, and the mixture was stirred to obtain a dispersion of conductive particles 2. 10 ml of a 1 mass % aqueous solution of benzotriazole was added to this dispersion, and the mixture was stirred for 5 minutes to perform a surface treatment. Thereafter, the mixture was filtered through a membrane filter with an opening of 2.0 μm, and conductive particles 2 having a benzotriazole layer on the surface were collected. The collected conductive particles 2 were washed with pure water, and then 100 ml of pure water was added to obtain a dispersion of conductive particles 2 having a benzotriazole layer on the surface. The insulating particles 4 obtained above were added to this dispersion liquid, and the mixture was stirred at room temperature (25°C) for 15 hours. After the insulating particles 4 were added, the solid-liquid concentration of the insulating particles 4 in the dispersion liquid was 10,000 ppm by mass. After removing the supernatant, the particles were washed with pure water and then vacuum dried at 50°C to obtain a coated particle sample. The coverage and adhesion of the obtained coated particle sample were evaluated in the same manner as in Examples 1 to 9, and the results are shown in Table 2.

[0150] Example 11 25 ml of toluene was added to the conductive particles 2 (5 g) obtained above, and the mixture was stirred to obtain a dispersion of conductive particles 2. 0.1 g of isopropyl triisostearoyl titanate (Ajinomoto Fine-Techno, Plainact KR-TTS) was added to this dispersion, and the mixture was stirred at room temperature for 20 minutes to perform surface treatment. After that, the mixture was filtered through a membrane filter with an opening of 2.0 μm, and conductive particles 2 having a titanate-based coupling agent layer on the surface were collected. 100 ml of a mixture of ethanol:pure water = 75:25 by mass was added to the collected conductive particles 2 to obtain a dispersion of conductive particles 2 having a titanate-based coupling agent layer on the surface. The insulating particles 4 obtained above were added to this dispersion liquid, and the mixture was stirred at room temperature (25°C) for 15 hours. After the insulating particles 4 were added, the solid-liquid concentration of the insulating particles 4 in the dispersion liquid was 10,000 ppm by mass. After removing the supernatant, the particles were washed with pure water and then vacuum dried at 50°C to obtain a coated particle sample. The coverage and adhesion of the obtained coated particle sample were evaluated in the same manner as in Examples 1 to 6, and the results are shown in Table 2.

[0151] [Table 2]

[0152] <Evaluation of electrical conductivity> An insulating adhesive containing 100 parts by mass of epoxy resin, 150 parts by mass of hardener, and 70 parts by mass of toluene was mixed with 15 parts by mass of the coated particle sample obtained in the example to obtain an insulating paste. This paste was applied to a silicone-treated polyester film using a bar coater, and then the paste was dried to form a thin film on the film. The obtained thin film-forming film was placed between a glass substrate with aluminum deposited on the entire surface and a polyimide film substrate with a copper pattern formed at a pitch of 50 μm, and an electrical connection was made. The conductivity of the coated particles was evaluated at room temperature (25 ° C, 50% RH) by measuring the conduction resistance between the substrates. The lower the resistance value, the higher the conductivity of the coated particles can be evaluated. The conductivity evaluation of the coated particles was performed as follows: a resistance value of less than 2 Ω was evaluated as "very good" (indicated by "◯" in Table 3), a resistance value of 2 Ω or more but less than 5 Ω was evaluated as "good" (indicated by "△" in Table 3), and a resistance value of 5 Ω or more was evaluated as "poor" (indicated by "x" in Table 3). The results are shown in Table 3.

[0153] [Table 3]

Claims

1. A coated particle in which the surface of a conductive particle having a metal coating formed on the surface of a core particle is coated with an insulating particle, the insulating particle being characterized in that a compound or a condensation product thereof containing a functional group having an electric charge is fixed to the surface of a silica particle having an uneven surface, and the silica particle having an uneven surface is a particle in which a smaller silica particle is bonded to the surface of a larger silica particle.

2. 2. The coated particle according to claim 1, wherein the core particle is made of a resin or a composite material of an organic substance and an inorganic substance.

3. 3. The coated particle according to claim 1, wherein the metal coating is at least one coating selected from the group consisting of nickel, palladium, gold, a nickel alloy, a palladium alloy, and a gold alloy.

4. 4. The coated particle according to claim 1, wherein the conductive particle has a plurality of protrusions on the metal coating.

5. 5. The coated particle according to claim 1, wherein the charged functional group is a group selected from the group consisting of a phosphonium group, an ammonium group, a mercapto group, and a sulfonic acid group.

6. 6. The coated particles according to claim 1, wherein the conductive particles are surface-treated with a hydrophobizing agent.

7. 7. The coated particles according to claim 6, wherein the hydrophobizing agent is a benzotriazole-based compound or a titanate-based coupling agent.

8. A conductive material comprising the coated particles according to claim 1 and an insulating resin.

Citation Information

Patent Citations

  • Conductive particle

    JP2013020721A

  • Conductive particle with insulative particles, manufacturing method of conductive particle with insulative particles, conductor material, and connection structure

    JP2013175453A

  • Colloidal silica having silica particle with unevenness on the surface, method for manufacturing the same, and polishing material using the same

    JP2013227168A

  • Conductive particles with insulating particles, conductive material, and connection structure

    JP2014029857A

  • Conductive film and connection structure

    JP2014241281A